Orientamento universitario in entrata: misurare l'efficacia - Laura Occhini (LED Edizioni Universitarie, 2018)
Considering the evident socio-cultural changes of the last few years, the university - and even more so degree courses - must review their training offer to align themselves with the demands of a constantly changing world of work. In this context, incoming orientation program, is fundamental. Therefore, for orientation services, it seems necessary to have effective tools to detect the needs and motivations of potential students enrolled and point out areas in which to invest time and resources. In this work tried to develop an instrument that was able to measure: the motivation to the university course choice, the power and the value of the motivation for the subsequent enrollment in the course but, above all, the level of influence they had in the choice of the various services and the various subjects deployed to the orientation of the students of the last year of high school. 190 freshmen enrolled in the degree course in Education Sciences of the University of Siena were tested with results that seem to confirm the validity of the procedure.